On the Dirichlet problem for de ge nerate Beltrami equations - Gutlyanskiĭ, V.Ya.; Ryazanov, V.I.; Sevost’yanov, E.A.; Yakubov, E. (Reports of the National Academy of Sciences of Ukraine, 2023)
We study the Dirichlet problem as with continuous boundary data in arbitrary simply connected bounded domains D of the complex plane where f satisfies the degenerate Beltrami equation a. e. in D. We give in terms of the BMO and FMO criteria as well as a number of other integral criteria on the existence and representation of regular discrete open solutions to the stated above problem.